Zooming into the complex dusty envelopes of C-rich AGB stars. Issue Volume 14:Issue S343(2019) (August 2018) - Lykou, Foteini; Hron, Josef; Klotz, Daniela
Abstract: Recent advances in high-angular resolution instruments (VLT and VLTI, ALMA) have enabled us to delve deep into the circumstellar envelopes of AGB stars from the optical to the sub-mm wavelengths, thus allowing us to study in detail the gas and dust formation zones (e.g., their geometry, chemistry and kinematics). This work focuses on four (4) C-rich AGB stars observed with a high-angular resolution technique in the near-infrared: a multi-wavelength tomographic study of the dusty layers of the circumstellar envelopes of these C-rich stars, i.e. the variations in the morphology and temperature distribution.